Interdecadal Change of Drought Characteristics in Mahaweli River Basin of Sri Lanka and the Associated Atmospheric Circulation Difference - Lin, Zhaohui; Shelton, Sherly (Frontiers in Earth Science, 2020)
Understanding the spatiotemporal characteristics of drought at the river basin scale is vital for water resources management. In this study, the interdecadal variation of drought characteristics over the Mahaweli River Basin (MRB) in Sri Lanka was investigated for the 1985-2015 period, using the standardized precipitation-evapotranspiration index (SPEI). Remarkable interdecadal change of yearly drought characteristics between 1985-1999 and 2000-2015 periods in the wet region of MRB can be found for medium-term and long-term drought, with indications of that more frequent and severer drought events as well as longer duration of total drought months, occurred during 2000-2015 period. Furthermore, interdecadal enhancement of yearly drought in the wet region can be attributed to changes of seasonal drought in southwest monsoon season, and this is coherent with the interdecadal shift of the SWM rainfall amount from wet to dry situations since the year 2000. However, no significant interdecadal change of drought was found in the intermediate and dry regions of MRB, as well as the short-term drought in the wet region. The interdecadal difference of atmospheric circulation demonstrates that the South Asian monsoon was weakened after 2000, which is accompanied by the weakening of monsoon trough, reduced cross-equatorial flow from the southern hemisphere from wind circulation at 850 hPa, and positive anomalies of geopotential height at 500 hPa over south Asian region. The weakening of South Asian monsoon leads to lesser moisture transport from the northwest Indian Ocean to Sri Lanka, inducing net moisture divergence anomalies in Sri Lanka, and ultimately results in more drought events during SWM season in the region since the year 2000.